Geometry Analysis and Force Simulation of a Kicker System’s Flat Solenoid to Robots for the Robocup Small Size League Category - Santos, Danillo Do N.; Silva, Guilherme S. A. e; Silva, Ítalo R. A.; Motta, Pedro S. V.; Souza, Júlia D. T. de; Araújo, Joaquim E. A.; Cajueiro, João P. C.; Silva, Pedro J. L. Da; Pinto, Adam H. M.; Researcheris, Bernard D. (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2021)
This paper presents the mechanical and electrical design of a solenoid used in the kicker system of a soccer-playing robot for RoboCup’s Small Size League (SSL) category. Old versions of the robots only kicked the ball forward, while this new project should also kick the ball upward (chip kick). The robot dimensions in this category are limited by the rules, so the new solenoid should apply at least the same force as the old one while occupying less space. Minding these limitations, the final robot design chosen is a flat rectangle with rounded edges instead of the default cylinder shape. With this research, we expect to encourage others to develop their solenoids according to specific needs, once there is a shortage of information in the community. The first round of design optimization used Finite Element Method Magnetics (FEMM), a 2D simulation software, using a Python script. The second step of design optimization was in 3D design, using Ansys Discovery AIM to optimize selected geometric parameters. Therefore, this two software complement each other, providing all the necessary resources to validate the project.